Indirect determination of chloride and sulfate ions in alcohol fuel by capillary electrophoresis - Pereira, E. A.; Stevanato, A.; Cardoso, A. A.; Tavares, MFM (Springer, 2004)
A capillary zone electrophoresis method using indirect UV detection for the analysis of chloride and sulfate in alcohol fuel samples was developed. The anions were analyzed in less than 3 min using an electrolyte containing 10 mmol 1(-1) chromate and 0.75 mmol 1(-1) hexamethonium bromide (HMB) as electroosmotic flow modifier. Coefficients of variation were better than 0.6% for migration time (n = 10) and between 2.05 and 2.82% for peak area repeatabilities. Analytical curves of peak area versus concentration in the range of 0.065-0.65 mg kg(-1) for chloride and 0.25-4.0 mg kg(-1) for sulfate were linear with coefficients of correlation higher than 0.9996. The limits of detection for sulfate and chloride were 0.033 and 0.041 mg kg(-1), respectively. Recovery values ranged from 85 to 103%. The method was successfully applied for the quantification of sulfate and chloride in five alcohol fuel samples. The concentration of sulfate varied from 0.45 to 3.12 mg kg(-1). Chloride concentrations were below the method's LOD.
Keywords: capillary electrophoresis; inorganic anions; alcohol fuel